Debtor-in-possession financing, loan-to-loan, and loan-to-own - Li, Kai; Wang, Wei (Journal of Corporate Finance, 2016)
This paper provides new evidence on the roles and strategies adopted by different types of debtor-in-possession (DIP) lenders: “loan-to-loan” (LTL) lenders—prepetition secured bank lenders providing DIP financing, and “loan-to-own” (LTO) lenders—activist investors (i.e., hedge funds or private equity funds) providing DIP financing. We find that LTL is more likely in Chapter 11 firms with better operating performance, when prepetition bank lenders' stakes are at risk, or when they have prior lending relationships with the distressed borrower. In contrast, LTO is more likely in small firms or when prepetition bank lenders' loans are over-collateralized. Finally, we show that much of the governance improvement at the emergence is attributed to LTO lenders. We conclude that creditors of different institutional types adopt distinct strategies to enforce their control rights under Chapter 11 reorganization and to have contrasting effects on the governance outcomes of emerged firms.